2013
DOI: 10.1093/nar/gkt204
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin KIFC1 actively transports bare double-stranded DNA

Abstract: During the past years, exogenous DNA molecules have been used in gene and molecular therapy. At present, it is not known how these DNA molecules reach the cell nucleus. We used an in cell single-molecule approach to observe the motion of exogenous short DNA molecules in the cytoplasm of eukaryotic cells. Our observations suggest an active transport of the DNA along the cytoskeleton filaments. We used an in vitro motility assay, in which the motion of single-DNA molecules along cytoskeleton filaments in cell ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
(52 reference statements)
1
36
0
Order By: Relevance
“…Interestingly, most KIF5B labeled dysferlin-containing vesicles did not show long-range processive movement and are limited to local movements in resting L6 myotubes. These findings are consistent with reports describing processive and non-processive movements of kinesin-bound cargoes (36,37). Possible explanations for the non-processive behavior of a subpopulation of kinesin-containing dysferlin vesicles are that KIF5B may be bound to dysferlin-containing vesicles without sufficiently activating kinesin motor activity or without actively engaging microtubules (36) or perhaps the clustering of vesicles limits their motility or anchors them to another subcellular structure.…”
Section: Dysferlin-containing Vesicles Move Along Microtubules Via Kisupporting
confidence: 91%
“…Interestingly, most KIF5B labeled dysferlin-containing vesicles did not show long-range processive movement and are limited to local movements in resting L6 myotubes. These findings are consistent with reports describing processive and non-processive movements of kinesin-bound cargoes (36,37). Possible explanations for the non-processive behavior of a subpopulation of kinesin-containing dysferlin vesicles are that KIF5B may be bound to dysferlin-containing vesicles without sufficiently activating kinesin motor activity or without actively engaging microtubules (36) or perhaps the clustering of vesicles limits their motility or anchors them to another subcellular structure.…”
Section: Dysferlin-containing Vesicles Move Along Microtubules Via Kisupporting
confidence: 91%
“…In addition to its mitotic spindle-specific roles, several other roles of HSET requiring or independent of its motor activity have been suggested such as a role in processing early endocytic vesicles [35], rat spermatogenesis [36] and active transport of bare double-stranded DNA [37]. Although it is presently unclear whether HSET performs all these functions in cancer cells, these studies bring to light the possibility that HSET's involvement in tumor biology could be multifaceted.…”
Section: Discussionmentioning
confidence: 99%
“…Such as, KIFC1 is associated with the nuclear membrane and acrosome in round and elongating spermatids (15) and is required for chromosome congression and alignment during mitosis (16). Farina et al reported that depletion of KIFC1 significantly decreases double-stranded DNA transport, which might provide new insight for gene therapy and DNA-based therapy (17). The exchange of intracellular substances is the driving force for the survival of cells, even more so for cancer cells.…”
Section: Original Articlementioning
confidence: 99%